Multiscalar Toxicities: Counter-Mapping Worker’s Health in the Nail Salon - Shadaan, Reena (Labour / Le Travail)

(untitled) (Canadian Committee on Labour History, 2024)
This article analyzes nail technicians’ occupational health experiences using body and hazard mapping – a visual, low-cost, and worker-centred approach. Thirty-seven Torontobased nail technicians from predominantly Vietnamese, Chinese, and Korean communities identified various occupational illnesses, injuries, and symptoms on visual representations of human bodies (body mapping) and linked these to their hazard sources in the nail salon (hazard mapping). The impacts identified include musculoskeletal aches and pains, stress and mental health concerns, various symptoms linked to chemical exposure, and concerns about cancer and reproductive health. Rather than a conventional occupational health approach, this work draws on Vanessa Agard-Jones’ expansion of the “body burden” as more than the bioaccumulation of chemical agents. As such, this article asserts that nail technicians’ body burden encompasses various types of occupational illnesses and injuries. In addition, nail technicians are exposed to broader “toxic” systemic inequities and structural conditions that allow these workplace exposures to occur and persist. By illustrating the embodied and experiential knowledges of nail technicians and contextualizing this lived experience, the body and hazard maps illuminate vast layers of harm – or multiscalar toxicities – borne by nail technicians. Moreover, as a group-based method, body and hazard mapping allow collective reflection and can spur worker mobilization toward safer and fairer nail salons.